(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Іntroduction. The Covid-19 pandemic, environmental changes and the economic crisis are changing the conditions and principles of business today. Nowadays, there are special requirements and restrictions need to be applied to operation of commercial enterprises, in particular – to the field of retail . The retail market should implement modern management methods, innovative technologies and sales tools to overcome the effects of the crisis. The purpose of the article. The purpose of the article is to investigate the development trends of the retail market in Ukraine; outline the main priorities and opportunities for further effective operation. Results. Domestic trade is an important area of economic growth, as it accumulates more than 13% of GDP in Ukraine. The modern retail market shows annual growth and it belongs to the most rapidly developed segments of the Ukrainian economy. It is represented by a wide variety of forms of interaction between seller and buyer. Some companies work on a narrow target audience, others focus on mass sales - belong to the field of retail. In 2019 retailers provided 72.5% of retail sales. The main features of the retail market in Ukraine are: annual growth of turnover, number of shops and retail space; development of franchise networks; growth of own brands; increasing logistics capacity; low level of market concentration and high intensity of competition; emphasis on the formation of positive consumer demand; increasing corporate social responsibility. Priorities in the development of retail market should be focused on such areas: providing safety for buyers and convenient services offline; growth of e-commerce; development of information technologies in the field of retail; increase share in trade for retailers of their own brands (private label), partial replacement of supermarkets with discount stores and shops close to the houses. Сonclusiоns. Ukrainian retail market shows annual growth and it is one of the fastest growing segments in Ukrainian economy. The consequences of the economic crisis and quarantine restrictions will affect the activities of Ukrainian retailers. This requires adaptation of trading methods to new conditions and intensification of innovative activities in the field of retail trade.